EFFECTIVENESS OF BIOFEEDBACK IN THE CLOSED LOOP OF HEART RATE VARIABILITY AND PACED BREATHING IN THE PATIENTS WITH SOMATOFORM AUTONOMIC DYSFUNCTION - Morozova, K. E.; Basnet, R.; Belal, S. A. S.; Martynenko, O. V.; Yabluchansky, M. I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
To study the effectiveness of biofeedback (BFB) in the closed loop of heart rate variability (HRV) and paced breathing in patients with somatoform autonomic dysfunction (SAD) 20 patients with SAD (14 women and 6 men, mean age 19,53 ± 1,55) were examined. All probationers were divided into two groups comparable for sex and age: 1 – BFB group (15 patients), in which 7 sessions was held and 2 – the comparison group (5 patients), where only two sessions were completed -at the first and seventh day of the study. Additionally, all patients in both groups received diet food (Table № 10 by Pevzner), mebicar, glycine, tiotriazolin. Effectiveness of biofeedback was evaluated by comparing of parameters optimality (O), sensitivity (S), the efficiency (E) and the integral index BQI in both groups. It was determined that biofeedback in the closed loop of HRV and paced breathing allows to optimize the state of the regulatory systems of the body in patients with SAD, moreover the combination of biofeedback sessions in the test loop and medical treatment are significantly better than isolated pharmacological therapy. High effectiveness of biofeedback in closed loop of HRV and paced breathing in patients with SAD allows us to recommend it as independent method of treatment, and as a component of combined therapy of this disease.